2022
DOI: 10.3390/pr10091796
|View full text |Cite
|
Sign up to set email alerts
|

Data Augmentation to Support Biopharmaceutical Process Development through Digital Models—A Proof of Concept

Abstract: In recent years, monoclonal antibodies (mAbs) are gaining a wide market share as the most impactful bioproducts. The development of mAbs requires extensive experimental campaigns which may last several years and cost billions of dollars. Following the paradigm of Industry 4.0 digitalization, data-driven methodologies are now used to accelerate the development of new biopharmaceutical products. For instance, predictive models can be built to forecast the productivity of the cell lines in the culture in such a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In this indirect method, the loss function is not directly linked to the neural network outputs (Pinto et al, 2022). As the data‐driven model is trained indirectly in the optimization framework, a regularization term can also be included in the fitness function (E wr ) to improve training convergence (Botton et al, 2022; Yang et al, 2011) as shown in Equation (6). Ewr=1n×mi=1nj=1m(ξijξˆij)2σξi2+λg, ${E}_{wr}=\frac{1}{n\times m}\sum _{i=1}^{n}\sum _{j=1}^{m}\frac{{({\xi }_{ij}-{\hat{\xi }}_{ij})}^{2}}{{\sigma }_{{\xi }_{i}}^{2}}+\lambda \Vert g\Vert ,$where λ is the regularization parameter (weight), and g is the parameter for the data‐driven component.…”
Section: Hybrid Modeling Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this indirect method, the loss function is not directly linked to the neural network outputs (Pinto et al, 2022). As the data‐driven model is trained indirectly in the optimization framework, a regularization term can also be included in the fitness function (E wr ) to improve training convergence (Botton et al, 2022; Yang et al, 2011) as shown in Equation (6). Ewr=1n×mi=1nj=1m(ξijξˆij)2σξi2+λg, ${E}_{wr}=\frac{1}{n\times m}\sum _{i=1}^{n}\sum _{j=1}^{m}\frac{{({\xi }_{ij}-{\hat{\xi }}_{ij})}^{2}}{{\sigma }_{{\xi }_{i}}^{2}}+\lambda \Vert g\Vert ,$where λ is the regularization parameter (weight), and g is the parameter for the data‐driven component.…”
Section: Hybrid Modeling Strategiesmentioning
confidence: 99%
“…This exercise can be repeated unless the projected best process conditions get stabilized (Figure 6). In silico generation of simulated batch experiments with a semi‐parametric hybrid has been shown to improve product titer, while deciphering the correlation between critical process parameters and critical quality attributes (Botton et al, 2022).…”
Section: Generalization Capabilities—how To Ensure?mentioning
confidence: 99%
See 2 more Smart Citations